Improvement of relationship mechanism in the system «client-bank» - Колодізєв, Олег Миколайович; Максімова, Марина Валеріївна (Technology audit and production reserves, 2016)
Provisions for improvement of relationship mechanism in the «Client-Bank» system through the use of a balanced scorecard are proved in the article. Analysis of the literature revealed the advantages and disadvantages of using the «Client-Bank» system for both customers and banks. Therefore, in order to improve the «Client-Bank» system author used a modern strategic management tool as balanced scorecard. Applying balanced scorecard provides for building a strategy map that reflects the objectives of the bank and the factors of achievement within each balanced option (finance, relationships with customers, internal business processes, and staff training and development) and reveals the causal relationships. Formed strategic map is the basis for the formation of a balanced scorecard assessing the quality of the «Client-Bank» system, which combines strategic objectives and strategic performance within each balanced option (finance, relationships with customers, internal business processes and staff training and development). The use of this system in practice allows realizing the strategy and objectives of the bank and will increase the efficiency of the «Client-Bank» system.